Nutrient Digestibility, N Balance, Performance, and Blood Parameters of Kacang Goats Differing in GDF9 Genotype Fed Different Sources of Dietary Fiber - Irawan, A.; Hartatik , T.; Bintara, S.; Astuti, A.; Kustantinah (Faculty of Animal Science, IPB University, 2024)
This study aims to determine the impact of different GDF9 genotypes on feed intake, nutrient digestibility, and nitrogen balance in Kacang goats by examining various metabolic processes. Twenty-nine Kacang goats were genotyped using PCR-RFLP DNA at position g.3855A/C of the GDF9 gene in exon 2. A 2 × 2 factorial design with two factors, namely, diet type (diets 1 and 2) and genotype (homozygote AA and heterozygote AC), was adopted. Diet 1 group comprised 11 goats with the AA genotype and 4 goats with the AC genotype, and the diet 2 group consisted of 9 goats with the AA genotype and 5 goats with the AC genotype. Both diets had the same protein content (iso-protein) and consisted of free-choice Napier grass (Pennisetum purpureum). Diet 1 had an additional 400 g of concentrate containing 11.25% crude protein (CP) and 55.86% total digestible nutrients (TDN). Diet 2 was a total mixed ration (TMR) containing 12.46% crude protein and 67.92% TDN. Results demonstrated a significant interaction (p<0.05) effect between diet and genotype on crude protein (CP) digestibility, neutral detergent fiber (NDF) digestibility, fecal nitrogen (N feces), urinary nitrogen (N urine), nitrogen retention (%), and blood urea nitrogen (BUN). However, no significant interaction effect was observed on the consumption of dry matter (DM), CP, crude fiber (CF), nitrogen free extract (NFE), and NDF and the digestibility of DM, CF, and NFE. TMR resulted in a 9% higher consumption of NDF, higher nutrient digestibility, improved nitrogen balance, average daily gain (ADG), and elevated glucose levels compared with diet 1. Kacang goats with the AC genotype exhibited better CP digestibility and increased nitrogen intake than those with the AA genotype. In conclusion, the GDF9 genotype influences the nutrient digestibility in Kacang goats, and those with the AC genotype utilize feed nutrients more efficiently than those with the AA genotype. The AC genotype resulting from the GDF9 gene mutation at position g.3855A>C can be used for genomic marker selection of high-quality Kacang goats in nutrient digestibility.